Access to Energy : 2000 and After - Conant, Melvin (Book collections on Project MUSE., 2015)
Conant explores how the transformation of oil from a commercial commodity to a strategic raw material have changed the face of world energy politics. In an increasingly interdependent world, Conant questions the right of any nation to withold vital supplies from other countries.